Physiological quality of graniferous sorghum seeds during storage - Rodrigues, Gabrielly Bernardes (2020)
The present study aimed to evaluate the effect of different drying temperatures and storage times on the physiological quality of graniferous sorghum seeds. Graniferous sorghum seeds were manually harvested after maturation, with moisture content of approximately 21% d.b., in the municipality of Jataí – GO, Brazil. The seeds were then dried in a forced air circulation oven at controlled temperatures of 40, 50, 60 and 70 °C until a final moisture content of 12 ± 1% d.b.. The seeds were stored in kraft paper packages for six months under laboratory conditions and evaluated for: moisture content, electrical conductivity, emergence in sand, emergence speed index, seedling length, seedling dry matter and accelerated aging. Parameters such as emergence, accelerated aging and seedling length decreased along storage, whereas electrical conductivity increased over time.